HUBUNGAN KELENGKAPAN IMUNISASI DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA ANAK BALITA DI WILAYAH KERJA PUSKESMAS SAWIT SEBERANG KECAMATAN SAWITSEBERANG KABUPATEN LANGKAT TAHUN 2017 - FEBI DWI DESIYANA; Zulhaida Lubis; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Acute Respiratory Infection (ARI) is a major cause of infectious morbidity and mortality in infants and children, especially in developing countries with low per capita income and medium income including Indonesia. According to the Ministry of Health of the Republic of Indonesia, the incidence of Acute Respiratory Infection in developing countries shows that there are 151 million (96.7%) new sufferers in the world of year. Acute Respiratory Infection is the top ranking disease of 10 major diseases with percentage of 12.4% (384 persons) in underfives at Sawit Seberang Health Center in 2016. This study aims to determine the relationship between completeness immunization with the incidence of Acute Respiratory Infection in toddlers. Types of this reseaech was descriptive by cross sectional design. The population in this study were all children under five years old (12-59 months) in the working area of ​​Sawit Seberang Community Health Center and 90 samples ware of 3,098 toddlers by accidental sampling. Data obtained using the questionnaire sheet completeness of immunization and acute respiratory infection incidence in infants. Data analysis using Chi-Square test with 95% confidence level. The result of this research shows that the incidence of Acute Respiratory Infection in toddlers in the working area of ​​Sawit Seberang Public Health Center as 47.8%.The result of bivariate analysis showed that the immunization has significant correlation with the incidence of Acute Respiratory Infection in toddlers that was p = 0,020. It is hoped that the Sawit Seberang Comminity Public Health Center provide counseling on the benefits and role of immunization for infants to prevent the occurrence of morbidity and mortality caused by the incidence of acute respiratory infections (ARI) and other diseases. Keywords:Acute Respiratory Infection incidence, completeness of immunization, children under five